The prevalence of VAIN, CIN, and related HPV genotypes in Japanese women with abnormal cytology - Zhang, Shitai; Saito, Mayumi; Yamada, Sumire; Sakamoto, Jinichi; Takakura, Masahiro; Takagi, Hiroaki; Sasagawa, Toshiyuki (Journal of medical virology, 2020)
Vaginal intraepithelial neoplasia (VAIN) is often found by chance. We investigated the prevalence of VAIN and related human papillomavirus (HPV) types in comparison with cervical intraepithelial neoplasia (CIN). This study enrolled 648 women who were referred to the outpatient clinic of Kanazawa Medical University Hospital for abnormal cytology from January 2009 to January 2019. HPV genotypes were determined using Genosearch‐31 + 4, which can detect 35 different HPV types. Colposcopy was performed at the first visit by an experienced gynecological oncologist. Among 611 subjects with squamous cell lesions, 107 (17.5%) VAIN cases were identified, and 67 (11.0%) women had both VAIN and CIN. Ultimately, 72 VAIN1, 15 VAIN2/3, 203 CIN1, 249 CIN2/3, 32 cervical squamous cell carcinomas (SCC), and one vaginal SCC (Vag‐SCC) were identified. The prevalences of VAIN1, VAIN2/3, and Vag‐SCC were 35.5%, 6.0%, and 3.1% of equivalent cervical lesions, respectively. The VAIN patients were older than the CIN patients (P = .002). About half of the VAIN cases were diagnosed during the follow‐up. Multiple HPV infections were found in 42.9% of the VAIN and CIN patients. HPV52, 16, 51, 53, and 56 were the most common types in VAIN, whereas HPV16, 52, 58, 51, and 31 predominated in CIN. HPV18 was rare in VAIN, HPV58 was more common in CIN than in VAIN, and HPV53 and HPV73 were more common in VAIN. In conclusion, VAIN1 was identified more frequently than we expected. Various HPV types were identified in the vagina, which is likely a reservoir for HPV. Highlights Prevalence of VAIN, CIN, and related HPV types.